Impact of Periodontal Diseases on Health-Related Quality of Life of Users of the Brazilian Unified Health System - Pamella Valente Palma; Paula Liparini Caetano; Isabel Cristina Gonçalves Leite (Hindawi Limited, 2013)
Objective. This study assessed the impact of periodontal diseases on health-related quality of life of adult users of the Brazilian Unified Health System. Study Design. A cross-sectional study was conducted on an outpatient basis. The sample included 151 adults treated in the Periodontics section at Dental Specialty Centres of Juiz de Fora (Minas Gerais, Brazil). The Oral Health Impact Profile (OHIP-14) measured the impact of periodontal disease on quality of life. Participants were interviewed to obtain self-perception of general and oral health and socioeconomic data, and dental records were consulted to obtain periodontal status data. The values of central tendency of the OHIP-14 were compared with socioeconomic, demographic, and self-reported health predictors using nonparametric tests. The final analysis was performed using multiple linear regressions. Results. The results showed that psychological discomfort and physical disability exhibited a negative impact. The following variables can explain approximately 27% of the impact of oral health conditions on health-related quality of life in this group: periodontal disease, self-perceived oral health, and the need to use or replace dental prosthesis. Conclusion. The need for prosthetic rehabilitation and worse periodontal status are associated with health-related quality of life, which can be predicted by the self-perception of health.